Pengaruh Peluang, Rasionalisasi Dan Kapabilitas Terhadap Fraud (Studi Kasus PT Sat Nusapersada Tbk Batam) - Nadila; Andi Auliya Ramadhany; Nur Isra Laili; Maya Richmayati; Khadijah (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2026)
This study aims to analyze the influence of opportunity, rationalization, and capability on the occurrence of fraud at PT Sat Nusapersada Tbk, Batam City. The study used a quantitative approach with primary data obtained through questionnaires distributed to 100 employees as respondents. Data processing was carried out using multiple linear regression analysis with the help of SPSS version 26. The results showed that the three independent variables had a positive and significant effect on fraud. Opportunity had a significance value of 0.004, rationalization of 0.002, and capability of 0.005. This indicates that the greater the opportunity, self-justification, and individual ability to exploit the situation, the risk of fraud also increases. The classical assumption test showed that the data were normally distributed and there were no problems of autocorrelation, multicollinearity, or heteroscedasticity, so the regression model was considered suitable for use. As a preventive measure, the company is advised to implement job rotation in the warehouse section, conduct periodic anti-collusion training, conduct risk-based audits in vulnerable operational areas, and provide ethics training to suppress rationalization and abuse of employee capabilities.